The biological activity of the probiotic strains of bacilli – base of the preparation endosporin - Safronova, L.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The biological activity of B. amyloliquefaciens ssp. plantarum strains, which are the base of the veterinary probiotic endosporin has been studied. It is shown that the strains exhibit the pronounced antagonism against pathogenic and conditionally pathogenic microorganisms, as well as bacteriolytic and yeastlytic activity, and synthesize antibiotics, complex proteolytic enzyme preparations, amino acids, and polysaccharides. The preparation is characterized by immunomodulatory and antitumor properties.